OPTIMIZING HUMANISTIC COMMUNICATION IN INTERGENERATIONAL INTERACTION IN TEENS COMMUNITY - Lobodally, Altobeli; Delliana, Santi; Humaira, Rabitha; Hermawan, Surya Dharma (Universitas Pelita Harapan, 2025)
The humanist communication training at Teens Community aims to improve intergenerational communication skills based on human values. In the era of Society 5.0, dependence on technology has reduced human interaction to medium-based communication, thus reducing the quality of face-to-face communication. Teens Community, a Christian youth community aged 12-18 years under the auspices of GBI Rosypinna, faces challenges in building effective and humanist communication, especially in delivering messages based on empathy, respect, and compassion. The training method involves delivering materials, group discussions, and interactive debates, which allow participants to practice intergenerational communication scenarios directly. The training was carried out in three stages: preparation, implementation, and evaluation, with materials arranged based on community needs. The results showed increased participants' understanding of the importance of humanist values ​​in communication. Participants could apply the principles of humanist communication, although this training was still partial. The literature supports that ongoing training is needed to strengthen the impact and sustainability of the program. The conclusion indicates that this training provides substantive benefits both for participants in improving communication skills and for the implementing team as an effort to apply knowledge. The program's continuation is recommended to create a more profound impact on the Teens Community in building communication based on humanist values.